Activated Flake Graphite Coated with Pyrolysis Carbon as Promising Anode for Lithium Storage. (1st April 2016) - Chen, Jun; Zou, Guoqiang; Zhang, Yan; Song, Weixin; Hou, Hongshuai; Huang, Zhaodong; Liao, Hanxiao; Li, Simin; Ji, Xiaobo
Abstract: A facile route to improve the lithium-storage properties of flake graphite (FG) is proposed through coating pyrolysis carbon from polyvinylidene fluoride (PVDF) assisted by KOH activation. The interplanar distance between the graphene sheets of activated PVDF/FG is enlarged, effectively suppressing the electrode deformation during lithium (de)-intercalation. More edge and porous structures of PVDF/FG arising from KOH activation on graphite flakes contribute to improved electron and ion transport, leading to great improvement in its rate and cycling performances. The initial specific capacity of the activated PVDF/FG is 476.6 mAh g −1  at 50 mA g −1 and when the current increases to 1000 mA g −1, the value still retains 142.6 mAh g −1 .